Optimization of Plasma Surface Modification for PET and PP Using Corona Treater in Microfluidic Applications - Jefri Dharmesta; Mohamad Baiquni; Mahfud Ibadi; Yudan Whulanza (International Journal of Engineering Continuity, 2025)
Plasma surface modification has proven to be an effective technique for enhancing the wettability and adhesion properties of polymeric materials, particularly in microfluidic applications. This study investigates the effects of corona plasma treatment on the surface properties of polyethylene terephthalate (PET) and polypropylene (PP) by analyzing surface roughness and contact angle measurements. Plasma treatment durations of 0, 30, 60, 120, and 180 seconds were applied to both materials. Scanning Electron Microscopy (SEM) revealed significant microstructural changes, with increased surface roughness and the formation of micro/nano-textures, enhancing fluid interaction. Contact angle measurements further confirmed the improved wettability, with PP decreasing from 96° (untreated) to 42° (180s plasma exposure), and PET from 93° to 18°, demonstrating PET’s superior retention of hydrophilic properties. However, excessive plasma exposure led to over-etching effects, particularly in PP, affecting surface uniformity. The results highlight the effectiveness of corona plasma treatment in enhancing the functionality of PET and PP for microfluidic applications, with PET exhibiting greater long-term stability. These findings provide valuable insights into the role of plasma modification in improving polymer surface properties, paving the way for advancements in biomedical and analytical microfluidic device fabrication.